Das representações docentes nas tramas de minémosine: Cartografias de sedição e sedução nos caminhos e atalhos da História da educação na ditadura militar (1964-1985). - Aleixo., Ramon de Alcântara (2013)
The aim of this research is to problematize Prata (Campina Grande PB) State School History lady teachers trajectories and memories during the dictatorship (1964-1985). Therefore, their trajectories are scrutinized, highlighting the contrasts in the interaction: public life versus private life during such period. It was necessary, thus, to broaden the concept of historical source , supporting its operationalization in the dialogue with New Cultural History. The categories practices , appropriations and representations guided this study, emphasizing the uses of curricula prescribed by the institutional power in its interface with five teachers private lives. As methodological approach, it was chosen the Thematic Oral History Methodology , associated with educational opinions, classroom diaries and newspapers in the city and in the state, in order to constitute these memories/histories. The uses of the prescribed curricula problematized through the reading practices and discussion point out the various appropriations of the act of consumption itself, far beyond the passive and reproductive perspective. Concerning the interaction public life versus private life in teachers routine, the aim was to problematize the fluid boarders, which are intersected in the constitution of new identities.